Glutathione S-Transferase Regulates Mitochondrial Populations in Axons through Increased Glutathione Oxidation - Smith, Gaynor A. (Neuron, 2019)
Mitochondria are essential in long axons to provide metabolic support and sustain neuron integrity. A healthy mitochondrial pool is maintained by biogenesis, transport, mitophagy, fission, and fusion, but how these events are regulated in axons is not well defined. Here, we show that the Drosophila glutathione S-transferase (GST) Gfzf prevents mitochondrial hyperfusion in axons. Gfzf loss altered redox balance between glutathione (GSH) and oxidized glutathione (GSSG) and initiated mitochondrial fusion through the coordinated action of Mfn and Opa1. Gfzf functioned epistatically with the thioredoxin peroxidase Jafrac1 and the thioredoxin reductase 1 TrxR-1 to regulate mitochondrial dynamics. Altering GSH:GSSG ratios in mouse primary neurons in vitro also induced hyperfusion. Mitochondrial changes caused deficits in trafficking, the metabolome, and neuronal physiology. Changes in GSH and oxidative state are associated with neurodegenerative diseases like Alzheimer’s. Our demonstration that GSTs are key in vivo regulators of axonal mitochondrial length and number provides a potential mechanistic link.